EFFECTIVENESS OF ZERO NEW STUNTING PROGRAM IN SUKABUMI CITY - Aulia, Vina Destiani; Sampurna, Rizki Hegia; Meigawati, Dine (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2024)
The purpose of this study was to determine the effectiveness of the zero new stunting program in Sukabumi City. The method used in this study was a quantitative research method with a descriptive approach. The population in this study were mothers who have toddlers in Sukabumi City, with a total of 100 samples. In this study, researchers used data collection techniques of observation, questionnaires/questionnaires, and literature study. In this study using a Likert scale measurement, with a Likert scale, the variables to be measured are translated into variable indicators. The results of this study indicate that the dimensions of achieving the goals of the zero new stunting program in Sukabumi City obtained a result of 75.8%. The integration of Sukabumi City Government in implementing the zero new stunting program in Sukabumi City obtained a result of 75.13%. And the success rate of adaptation of the zero new stunting program in Sukabumi City was 76.28%.